Analisis Komunikasi Dalam Meningkatkan Kinerja Pegawai Di Kantor Lurah Parung Serab Kecamatan Ciledug Kota Tangerang - Maulida, Wahyu; Asmalah, Lia (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to identify and analyze the impact of communication on improving employee performance at the Parung Serab Village Office, Ciledug District, Tangerang City. The research method used was descriptive qualitative, with data collection techniques including observation, interviews, and documentation with one key informant and five other informants. The results indicate that the communication process is quite good, with good relationships between employees and their superiors and among themselves. However, understanding of communication skills still needs to be improved. Employee performance is quite good, with the quantity of work performed commensurate with the amount of work assigned, good cooperation, and effective supervision. However, the quality of performance and the timeliness of tasks from superiors still need to be improved for future improvement.